THE EFFECTIVENESS OF FORMING BREASTFEEDING SUPPORT GROUP PROGRAM TO IMPROVE EXCLUSIVE BREASTFEEDING - Dewi Roudhotul Hasanah; Nuzulul Kusuma Putri; Andini Yulina Pramono (Indonesian Journal of Health Administration, 2020)
Background: Exclusive breastfeeding is a problem of maternal and child health in Indonesia. With Breastfeeding Support Group, exclusive breastfeeding is expected to improve. Sugihwaras Village and Sumbergede Village have been initiating Breastfeeding Support Group program. However, the framework of Breastfeeding Support Group program and intervention methods for pregnant and breastfeeding mothers in both villages were different.Aim: It analyzed the effectiveness of forming Breastfeeding Support Group program and intervention programs for pregnant and breastfeeding mothers to improve exclusive breastfeeding in Sugihwaras Village and Sumbergede Village.Methods: This study used a case study approach to the formation of Breastfeeding Support Group program. Comparative analysis was done descriptively by selecting samples from the Fieldwork Report of Group 14 and 15 in the period of 2017/2018, Faculty of Public Health, Universitas Airlangga. This study applied total sampling technique and descriptive analysis by comparing community’s characteristics (as input), a form of intervention and program management (as a process), and results of evaluating the formation of Breastfeeding Support Group (as an output).Results: Community’s characteristics in both villages tend to be similar, and the average duration of each program was the same. Sumbergede Village focused on the readiness of forming cadres for Breastfeeding Support Group program, while Sugihwaras Village focused on breastfeeding mothers and their husbands. Indicator analysis of the program showed that Sumbergede Village (80.00% achieved) had a 5.71% higher percentage of attainment compared to Sugihwaras Village (85.71% achieved). Analysis of the program’s strengths and weaknesses pointed out that Sumbergede Village had more values and power in resources in its region.Conclusion: The intervention program in Sumbergede Village tends to be more effective. It has greater potential to be a sustainable program in the following year to improve 100% exclusive breastfeeding. Keywords: Breastfeeding Support Group, exclusive breastfeeding, intervention, effectiveness.